The library humanistic mission under the information civilization conditions - G. M. Kormishina (Библиосфера, 2014)
Informatization in most cases is regarded as an absolute benefit to mankind. At the same time, there is an invisible struggle between informatization and humanization. The latest communication tools, expanding the possibilities of cultures intercourse, create a range of communicative and psychological problems at the same time. The author shows how computerization can threaten mankind. The essence of the fundamental paradoxes are: 1) «knowledge society» rapidly reproduces «society of persons knowing nothing» 2) «high» and «low» culture has interchanged, 3) in a huge communicating space the problem of meaning loss has exacerbated etc. Under such circumstances, the library is one of those institutions, which helps the individual, society to comprehend the information, to develop knowledge, to create new ones through a variety of communication processes. Just libraries can compensate a deficiency of communication, save a modern man from discomfort, overcome diverse processes orientation - information (intended for the mass users) and communicative (designed for personal and conscious perception) ones. As far as the majority of changes in a modern man existence act against humanity, the author believes, that the most urgent task of modern library science is to disclose a particular meaning of libraries humanistic mission, which have always been the humanistic social institution.